MERAJUT PERSAUDARAAN KOMUNITAS LEWAT KONFLIK (Studi Suporter Turnamen Sepak Bola Komodo Cup Manggarai NTT di Makassar) - Arda Senaman (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
Conflict prevention among the fans of Komodo Cup Football Tournament is achieved by the ability of officials to open upa discussion for the fans with the goal of controlling the actions that they undertake before and after the game. Conflict resolutions applied are: synchronization between the officials and the security officers so that every conflict can be prevented by persuasive approach, as well as by collaborations with the Government of Makassar. Moreover, conflict resolution was intensified by interactional approach with focused and unfocused interaction. Focused interaction is facilitated by officials through a meeting to discuss activities that they will do during a match. Meanwhile, unfocused interaction facilitates the interaction among supporters to make them feel needed and cared for. And the actors of the conflict are not grudge risk one each others.Keywords: Fostering Brotherhood, Football Fans Conflict, Persuasivbe Approach